Toward the issue of the essence and kinds of the international conflicts - Стрельцов, Євгеній Львович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
In the article there is examined the modern vision of the essence and kinds of international conflicts. The author paid attention to the necessity of the studying conflicts in modern Ukraine, causes of its arising and dynamic of development, as well as influence of transforming social and political system.